2023
DOI: 10.1002/batt.202300140
|View full text |Cite
|
Sign up to set email alerts
|

An Incremental Capacity Analysis‐based State‐of‐health Estimation Model for Lithium‐ion Batteries in High‐power Applications

Abstract: The Incremental Capacity (IC) is a rich source of data for the state‐of‐health estimation of lithium‐ion batteries. This data is typically collected during a low C‐rate (dis)charge of the battery which is not representative of many real‐world applications outside the research laboratories. Here, this limitation is showcased to be mitigated by employing a new feature‐extraction technique applied to a large dataset including 105 batteries with cycle lives ranging from 158 to 1637 cycles. The state‐of‐health of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…46 For this purpose, incremental capacity analysis (ICA) has been widely employed as a non-invasive in situ electrochemical technique to estimate the internal cell state and explore degradation mechanisms. 47 The ICA plots are obtained by differentiating the cell capacity over potential (i.e., dQ/dV) during charge or discharge, with the peaks representing the electrochemical reactions and phase transitions. Previously, we demonstrated that the peaks and features of ICA analysis on LFP-LTO coin-cells located at the same potential as those of the incremental strain analysis (ISA), obtained by differentiating the strain over potential (i.e., dɛ/dV), in the first 16 cycles.…”
Section: Sohmentioning
confidence: 99%
“…46 For this purpose, incremental capacity analysis (ICA) has been widely employed as a non-invasive in situ electrochemical technique to estimate the internal cell state and explore degradation mechanisms. 47 The ICA plots are obtained by differentiating the cell capacity over potential (i.e., dQ/dV) during charge or discharge, with the peaks representing the electrochemical reactions and phase transitions. Previously, we demonstrated that the peaks and features of ICA analysis on LFP-LTO coin-cells located at the same potential as those of the incremental strain analysis (ISA), obtained by differentiating the strain over potential (i.e., dɛ/dV), in the first 16 cycles.…”
Section: Sohmentioning
confidence: 99%
“…In contrast to increasing trend to use ICA, this method has trouble with real life application. [16] High current profiles, complex components and non-sensitive measurement makes coulomb counting inaccurate that directly affect SOH estimation as well. Therefore, ICA method by itself is inappropriate for on-board estimation.…”
Section: ∆𝑉mentioning
confidence: 99%
“…To overcome this limitation, a new feature extraction technique has been applied to a large data set of batteries with different cycling lifetimes. This technique uses three regression models, support vector regression (SVR), multilayer perceptron, and random forest, to successfully predict the health status of batteries 16 . Zhang et al 17 proposed a new method for estimating the SOH of batteries based on an integrated analysis of incremental capacity analysis (ICA) and SVR using a voltage‐capacity model.…”
Section: Introductionmentioning
confidence: 99%
“…This technique uses three regression models, support vector regression (SVR), multilayer perceptron, and random forest, to successfully predict the health status of batteries. 16 Zhang et al 17 proposed a new method for estimating the SOH of batteries based on an integrated analysis of incremental capacity analysis (ICA) and SVR using a voltage-capacity model. Xu 18 proposed a new method for estimating the SOH of LIBs based on discrete ICA.…”
mentioning
confidence: 99%